The European Pillar of Social Rights - Rainone, Silvia (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2020)
Social and labour policies have a significant relevance for the European Union`s (EU) economic agenda. First, it is generally assumed that lifting labour law rigidities helps firms to increase their competitiveness on the market. Labour market flexibility is indeed deemed to create a favourable environment for business and to support the employment rate. Second, the convergence of different national labour law systems is important to foster the expansion of European single market and to reduce the competitive advantage of companies situated in countries where labour costs are lower. It is in consideration of the EU social and labour policies` economic rationale that the author approaches the European Pillar of Social Rights (EPSR). This contribution places the origins of the Pillar in the EU economic agenda that followed the 2008 financial crisis and that was designed to resume European economic growth and productivity. As stated in the 2015 Five Presidents Report, the re-launch of EU economy depended on the deepening of the Economic and Monetary Union (EMU) which, in turn, needed greater focus on employment and on social performance. The author argues that the Pillar constitutes the bridge between the EU strategy for a deeper EMU and social and labour policies. This then raises the question on whether a social agenda rooted in an economic strategy is adequate to fulfil the Union`s objective to advance social progress and improve living and working conditions. The contribution illustrates that the policy documents that preceded the proclamation of the EPSR, the EPSR`s structure and content, and its implementation tools reflect the economic embedding. The accent is placed on labour market flexibility and inclusivity, job creation and entrepreneurship more than on promoting the upward convergence of labour and social standards. The author argues that the Pillar is ontologically linked to the deepening of economic integration and that it does not provide, per se, sufficient instruments to effectively promote social fairness. However, it is noted that much depends on how strong are the ties that link the Pillar with the economic agenda. If the EU institutions, and the Commission in primis, manage to de-contextualise the Pillar from its market deepening embedding, that could emancipate future social and labour policies from the overarching economic rationale.